The effects of using social networks on the self-esteem of adolescents and their attitude towards education and the future - Glušac, Dragana; Perić-Prkosovački, Bojana; Nikolić, Milan (Norma, 2022)
The paper presents a study aimed at determining the connection between the use of the Internet and social networks and the level of adolescent self-esteem and self-assessment of their own qualities and abilities, as well as determining the correlation between the social network use with children‘s educational aspirations. Adolescents’ attitudes towards people, fear of the future, their willingness to take risks, reading classic books and attitudes towards multimedia learning and reading were also detected. The research was conducted by examining the attitudes of adolescents aged 14 to 19 years. The data were obtained by processing N=599 questionnaires of a representative focused sample of adolescents - high school students in the Republic of Serbia. The research was conducted in 2021. Descriptive, correlation and regression analysis was used in data processing. Descriptive analysis showed that the lowest average score was achieved for the dimension related to reading classic books, and the highest for the dimensions of attitude towards people and fear of the future. Correlative analysis between the dimensions showed that self-esteem and the use of social networks are not related, but the more positive attitude towards education, the higher are standards and the more positive are attitudes towards people. A similar finding is in the regression analysis, which shows that what affects self-esteem is the value of one’s own standards, the attitude towards people, as well as the fear of the future.